Analytic morphometric assessment of patients undergoing colectomy for colon cancer. Issue 3 (11th July 2013) - Sabel, Michael S.; Terjimanian, Michael; Conlon, Anna S.C.; Griffith, Kent A.; Morris, Arden M.; Mulholland, Michael W.; Englesbe, Michael J.; Holcombe, Stephan; Wang, Stewart C.
Abstract Background Analytic morphometrics provides objective data that may better stratify risk. We investigated morphometrics and outcome among colon cancer patients. Methods An IRB‐approved review identified 302 patients undergoing colectomy who had CT scans. These were processed to measure psoas area (PA), density (PD), subcutaneous fat (SFD), visceral fat (VF), and total body fat (TBF). Correlation with complications, recurrence, and survival were obtained by t‐tests and linear regression models after adjusting for age and Charlson index. Results The best predictor of surgical complications was PD. PMH, Charlson, BMI, and age were not significant when PD was considered. SF area was the single best predictor of a wound infection. While all measures of obesity correlated with outcome, TBF was most predictive. Final multivariate Cox models for survival included age, Charlson score, nodal positivity, and TBF. Conclusions Analytic morphometric analysis provided objective data that stratified complications and outcome better than age, BMI, or co‐morbidities. J. Surg. Oncol. 2013; 108:169–175. © 2013 Wiley Periodicals, Inc.